Evaluation of the Implementation of a Home-Based Exercise Training Program for People With COPD: A Mixed-Methods Study - Cerini, Tamara; Kunz, Ramona; Dalla Lana, Kaba; Radtke, Thomas; Polhemus, Ashley; Puhan, Milo A.; Frei, Anja (Frontiers in Rehabilitation Sciences, 2021)
Introduction Recently, we developed the home-based, minimal-equipment exercise training program HOMEX for people with COPD and tested its effectiveness over one year in an RCT. The aims of the current study were to evaluate the implementation of HOMEX from the perspectives of all involved persons and to optimize the program to ensure its long-term sustainability. Methods In this mixed-methods study we used qualitative and quantitative approaches to evaluate the implementation of the intervention on the level of COPD patients, coaches who provided the intervention and relevant stakeholders. To assess the implementation outcomes dose, reach, fidelity and adherence, we summarized information recorded in coaches’ notes and patients’ diaries, complemented with results from qualitative assessments. To assess acceptability and appropriateness, we conducted surveys with patients and coaches and semi-structured interviews with selected patients, coaches and stakeholders. Results The coaches delivered the three home visits with one exception according to protocol (fidelity). Of the 53 intervention group participants, 37 (70%) conducted HOMEX training until study end and 43 (79%) trained for at least 10 months. The participants’ exercise behaviors could be separated into the phases “Starting the training and stabilizing into regular training routine” and “Managing training disruptions” (adherence). Overall, patients, coaches and stakeholders conveyed a very high acceptability of HOMEX, noting the home-based aspect as a particular strength and interaction with other patients as future need. All involved groups perceived the strength-training exercises as appropriate, efficient for people with COPD, and relevant to maintain improvements after pulmonary rehabilitation. The patients’ most important facilitators for long-term motivation were self-perceived improvement in strength, supervision by coach and integration of the training in daily routine. Based on these insights, we redesigned and reworded the exercise cards, introduced three new exercises and refined the training book. Discussion The results of this study provided insights of the involved persons in the frame of the HOMEX intervention implementation with particular focus on participants’ long-term training behavior and their perception and experience with the exercise program. These findings enabled us to optimize the training material and adapt the program’s structure for sustainable further use in clinical and other settings.